Mladi in življenje v obmejnih regijah Slovenije - Kolenc-Kolnik, Karmen (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1999)
This article present the results of research in which we worked with 523 Slovenian secondary school pupils who live in the border regions of Slovenia and Europe. Their opinion on the state border and multicultural diversity of border regions, their spatial identification and perspectives of their lives in different border regions are discussed
Keywords: ankete; državne meje; mladina; multikulturnost; obmejne regije; obmejno sodelovanje; povezovanje; Slovenia; Slovenija; srednješolci